Frequency and size change of ice-snow avalanches in the central Himalaya: A case from the Annapurna II glacier - Li, Yao; Cui, Yi-Fei; Hao, Jian-Sheng; Zhang, Zheng-Tao; Wang, Hao; Guo, Jian; Wang, Shuo-Fan (Advances in Climate Change Research, 2024)
Glaciers have retreated and shrunk in High Mountain Asia since the mid-20th century because of global warming, leading to glacier instability and hazardous ice-snow avalanches. However, the complex relationship between ice-snow avalanches and factors such as climate and potential triggers are difficult to understand because of the lack of observational data. Here, we addressed ice-snow avalanches on the Annapurna II glacier in Nepal, Central Himalaya. We constructed an ice-snow avalanche history using long-term multi-source remote sensing images (1988-2021) and mapped the velocity fields of glaciers using cross-correlation analysis on SAR and optical images. Then, we investigated the impact of climate change and earthquakes on the frequency and size of ice-snow avalanches. The results demonstrate that the frequency of ice-snow avalanches has increased from 10 in 1988 to 27 in 2020, but the average area of ice-snow avalanche deposits has decreased by approximately 70%, from 3.4 x 105 m2 in 1988 to 1.2 x 105 m2 in 2020. The evolutionary characteristic of ice avalanches is linked to the impact of glacier retreat (reduction in ice material supply) and increased activity under climate change. The glacier movement velocity controls the size of ice-snow avalanches and can be set as an indicator for ice-snow avalanche warnings. On the Annapurna II glacier, an ice-snow avalanche occurred when the glacier velocities were greater than 1.5 m d-1. These results offer insights into ice-snow avalanche risk assessment and prediction in high-mountain areas, particularly in regions characterised by dense glacier distribution.